Coupling transcription, RNA processing and RNA export - Hartzog, Grant (Henry Stewart Talks, 2007)
Mechanistic coupling of RNA processing, export and transcription, Current evidence supporting coupling mechanisms, Role of the RNA polymerase II CTD, Competition during transcription between RNA binding proteins, Future challenges and directions
Archived at 2022/04/13